Bayesian prediction in threshold autoregressive models with exponential white noise - Pereira, IMS (2011)
In this paper, we develop a Bayesian analysis of a threshold antoregressive model with exponential noise. An approximate Bayes methodology, which is introduced here; and the Gibbs sampler are used to compute marginal posterior densities for the parameters of the model; including the threshold parameter, and to compute one-step-ahead predictive density functions. The proposed methodology is illustrated with a simulation study and a real example.